The board and IT governance: The what, who and how - S. Posthumus; R. Von Solms; M. King (South African Journal of Business Management, 2010)
This paper discusses the importance of corporate governance and the need to implement it effectively in any organization. Furthermore, information technology is discussed along with its impact on enabling an organization to achieve its business goals and attain a competitive edge in industry. This makes IT a critical organizational resource with great strategic impact and necessitates that it be governed effectively through sound IT governance efforts. However, currently there seems to be a significant lack of board-level understanding with respect to the impact of IT on the business and therefore IT may not be adequately directed and controlled. To address this problem, a model is proposed in this paper to enable the board of an organization to develop an understanding of how to Issue directives and implement effective control over IT so that IT supports organizational business goals and continues to provide value to an organization.
Keywords: 650